Interpretasi Dampak Keuangan Keluarga Tenaga Kerja Wanita (Studi Fenomenologi TKW Pamekasan yang Berimigrasi ke Saudi Arabia dan Malaysia) - Agus Sugiono; Aminatus Zakhra; Evi Malia (AKUNTABEL, 2017)
This research tries to reveal how far the financial impact of migrant workers who migrate to Saudi Arabia and Malaysia. The method used is qualitative / non positivistic method (Non Mainstream) through understanding method (verstehen) with Interpretive Paradigm and Husserl Transcendental Phenomenology approach. The main informants in this study as many as 6 people while the relevant institutions, researchers made a second informant to confirm data about TKW. This research reveals that the financial impacts of TKW Pamekasan families who immigrated to Saudi Arabia and Malaysia do exist, although they are not very significant, but in their view are significant because they bring a lot of changes to their lives, especially in the form of "house and land assets", their children's education, Family life left behind and can pay family debts for some TKW indebted. The TKW Pamekasan has been able to change the original residence of "gedek" into a permanent building. In terms of education some TKW have managed to send their children to the level of secondary education and some even until college graduation. In addition, other financial impacts are the availability of venture capital for them to open new businesses either in the form of small "pracangan" stores or other businesses as a guarantee to survive after their return to Indonesia. While the other impact of "intangible property" that is in the form of satisfaction of the heart because it can fulfill the pillars of Islam to Lima (pilgrimage) for migrant workers who immigrate to Saudi Arabia.Keywords: Immigration, Family Financial Condition, Female Labor